PENGEMBANGAN PARIWISATA BERKELANJUTAN MELALUI PEMBERDAYAAN MASYARAKAT LOKAL DI DESA WISATA PAMPANG, SAMARINDA, KALIMANTAN TIMUR - Suhartapa; Evangelin Estevania Pelle (Jurnal Pariwisata Tawangmangu, 2026)
The active involvement of local communities is essential to the planning and development of tourism, especially in transforming rural areas into tourism villages rooted in local wisdom, a key element of sustainable tourism in Indonesia. This study employs a qualitative research approach. Data were collected through observation, interviews, and documentation. The results show that one of the main challenges faced by the local community is that those not directly involved in tourism development do not significantly feel the benefits. Additionally, limited human resources in digital promotion and English language skills hinder the development of Pampang Tourism Village. The development of Pampang Tourism Village requires efforts to improve community capacity through digital promotion training and English language education, broader community participation, enhanced product quality and marketing of local crafts, and improvements in facilities and the creation of more attractive tourism packages to increase the village’s competitiveness and sustainability. Future researchers are encouraged to explore strategies for training and capacity building in digital promotion, cross-cultural communication (especially English), and tourism business management.